Antimicrobial Properties and Cytotoxic Effect Evaluation of Nanosized Hydroxyapatite and Fluorapatite Dedicated for Alveolar Bone Regeneration - Wojciech Zakrzewski; Zbigniew Rybak; Magdalena Pajączkowska; Joanna Nowicka; Maria Szymonowicz; Agnieszka Rusak; Rafał J. Wiglusz; Katarzyna Szyszka; Jacek Chmielowiec; Grzegorz Chodaczek; Krzysztof Kujawa; Bartosz Mielan; et al. (Applied Sciences, 2024)
Background: Alveolar bone augmentation is a complex process influenced by a multitude of factors. The materials applied in augmentation procedures must be confirmed as non-toxic, and their physicochemical properties should allow proper bone reconstruction. The specifics of oral surgical procedures require the use of regenerative biomaterials with antimicrobial properties. This study focuses on the physicochemical characteristics of chosen nanosized biomaterials, as well as their cytotoxicity and antimicrobial properties. Methods: nanosized hydroxyapatite and fluorapatite (abbreviated as nHAp and nFAp) pellets were manufactured using a microwave hydrothermal synthesis method. The impact on Candida albicans, Streptococcus mutans, and Lactobacillus rhamnosus strains activity and adherence to apatites was tested. Cytotoxic evaluation was performed based on the differentiation process of MC3T3 cells. The effectiveness of MC3T3 differentiation was confirmed by Alizarin Red staining. Results: Contact with both biomaterials caused a reduction in the mean microbial count of S. mutans and C. albicans strains, as observed. Studied biomaterials demonstrated enhanced proliferation of MC3T3 cells, with the exception of the 1:1 nFAp concentration. Conclusions: Both biomaterials enhance the proliferation of fibroblasts and limit the activity of specific oral pathogens in vitro. The research clearly demonstrates the advantage of nFAp over nHAp, with a notable reduction in microbial count of Candida albicans and Streptococcus mutans over time. The lowest microbial count reduction was observed in the case of L. rhamnosus. Further research is required in order to fully understand the specifics of nHAp and nFAp antimicrobial action. However, the results were found to be more favourable for nFAp biomaterial.